Ordered vacancy compounds: the case of the Mangéli phases of TiO2 - Michejevs Padilha, Antonio Claudio; Rocha, Alexandre Reily [UNESP]; Dalpian, Gustavo Martini (Elsevier, 2022)
Defects typically appear in materials in very limited quantities, usually of the order of 1016-1019/cm3. In some cases, however, these defects can be observed in a much larger concentration, enough to change the stoichiometry of the parent compound and even change their crystal structure. An important class of these materials is the ordered vacancy compounds, first proposed for CdIn2Se4. Other compounds, such as hybrid perovskites, can also present ordered vacancy compounds, such as Cs2SnI6, derived from CsSnI3. In this chapter, we will discuss ordered vacancy compounds derived from the transition metal oxide compound TiO2. These are known as the Magnéli phases of TiO2 and can be constructed by removing oxygen atoms from the host lattice. There are several different polymorphs that can be created by changing the quantity of oxygen vacancies, including Ti2O3, Ti3O5, and Ti4O7 (based on the formula Ti n O2n−1). We will discuss the structural determination of these materials that can be created by sliding planes from the rutile TiO2 structure. Also, the electronic structure of these compounds is characteristic of intermediate band materials and can be directly correlated to the properties of oxygen vacancies in TiO2. Lastly, we will discuss the potential applications of this kind of materials that can include memristors and batteries.
Keywords: Computational simulation; Density functional theory; DFT; Magnéli phases; Memristive devices; Memristor; Titanium oxide